The Influence of Service Quality and Brand Image on Customer Satisfacation at BMR Tour And Travel Agent - Nugraha, Rizki Nurul; Meini, Zumratul (West Science Information System and Technology, 2024)
Tourism development is increasingly rapid with many increasing tourism trends. The increasing development of tourism causes an increase in demand for tours usually carried out by Tour and Travel, with this increase the quality of service and brand image is needed to produce customer satisfaction. This research uses descriptive quantitative methods to determine the magnitude of the influence of variables (X), namely Service Quality and Brand Image and variable (Y), namely Customer Satisfaction, using a regression research design. The data obtained by 30 respondents was then tabulated and analyzed using multiple linear regression tests using the SPSS version 22.0 program. The results of the research on the influence of service quality and brand image on customer satisfaction showed that the F-test results obtained were an F count of 55,523, which states that all Service Quality and Brand Image variables simultaneously and significantly influence the dependent variable (Customer Satisfaction).